UWARUNKOWANIA KSZTAŁTOWANIA STRUKTURY ORGANIZACJI PUBLICZNEJ NA PRZYKŁADZIE PODLASKIEGO URZĘDU WOJEWÓDZKIEGO - Madras, Tomasz (Management and Administration Journal, 2025)
The research presented in the article concerns the determinants of organizational structures in public organisation, particularly the influence of managerial attachment to existing, stable structures, using the example of the Podlaskie Voivodeship Office. For this purpose, an analysis of legal and organizational determinants was carried out, along with empirical research in the form of a survey conducted among a selected group of middle-level managers (head of departments) of the office. The conducted research illustrates the strength and specificity of the office staff’s attachment to stable, and often simply inherited, organizational structures. A two-dimensional character of the determinants shaping the organizational structure can also be observed, consisting of the interplay between external influences (specific legislation) and internal factors, with particular emphasis on organizational culture. The described structure proves to be very stable and therefore inflexible, with a deeply rooted sense of its own organic nature, where the effectiveness of a manager depends on an excellent understanding of the organization (internal recruitment) and where high levels of conformity and adaptation to the team of people they work with are expected from employees.